Effects of Diabetes on The Output of Farmer and Its Policy Implications - Naqvi, Syed Asif Ali; Hussain, Bilal; Shah, Syed Ale Raza; Makhdum, Muhammad Sohail Amjad (UI Scholars Hub, 2020)
This study investigated the impact of diabetes on work performance of different farming communities from Punjab, Pakistan. This study was based on cross-sectional data. A representative sample of 374 farmers was collected from five selected districts. Three types of respondents were analyzed in the study e.g.,laborer, small and large growers. Poisson and logistic regression techniques were used for the sake of analysis. According to the investigated results for thelabor category, respondents with more age, less qualification, low earning per month (Rupees), and having positive record of family diabetes, would havemore leave per month. In the same way, findings for small farmers revealed that education, family size, family with diabetic records, marital status and availability at farm (hour/day) were significant. In case of third category, study outcome highlighted that age, education, marital status, having positive record offamily diabetes and number of hours spent at farm would be positively correlated with the reduction in working efficiency at farm due to diabetes. It can beconcluded that diabetes have negative influence on the work performance of selected farming groups.